#TITLE_ALTERNATIVE# - HIDAYAT ( NIM : 15010007 ), RAHMAT
The temporary vertical evacuation building is set as refugee area or shelter when tsunami happen. Building is designed based on Maximum Considered Tsunami (MCT) using load design equivalent of a 2% probability of being exceeded in a 50- year period or a 2.500-year average return period. Besides that, the height of tsunami runup plan (R) is defined by tsunami inundation map. Planning model of temporary vertical evacuation building from tsunami have to meet the criteria that is established by FEMA P-646 with adaptations to regulations of buiding planning and designing in Indonesia. The performance level of structure must be determined as Immediate Occupancy (IO) or safe condition after earthquake occured. Means that structure is in good performance when tsunami happens. Progressive collapse is the important parameter that should be considered in tsunami evacuation building. The U.S. General Services Administration (GSA) developed the Proggressive Collapse Analysis and Design Guidelines for New Federal Office Buildings and Major Modernization Project using Column Removal Method to ensure that the potential for progressive collapse is addressed in the design and planning of building. Demand-Capacity Ratio (DCR) becomes the extreme condition that determining structure collapse parameter and is calculated by statis linier analysis of structure elements around removal column. Based on analysis that is done, the way to prevent it are by adding the capacity of section in changed loads distribution area when one or two columns remove and by reefing bay of structure to add redundancy of structure. System of stucture with good endurance to tsunami loads should have one of the criterias (1) strong and has back up ability to restrain the extreme loads; (2) open structure to minimize resistance caused by water flows; (3) ductile structure; (4) structure with enough redundancy.